Ocorrência, distribuição e caracterização de fungos entomopatogênicos em solo natural e cultivado - Azevedo, Ana Gorete Campos de (2013)
This study aimed to evaluate the occurrence and diversity of entomopathogenic fungi at Sergipe state, considering the factors that affect their distribution. The analysis was done using soil samples collected in the three mesoregions of the state in two periods of collection, comprising a wet and a dry season, and in two different habitats (agricultural and natural). Parameters such as pH, organic matter and argil soil were considered in the analyzes. For the soil fungi isolation, two methods were used, the soil solution in culture medium and selective insect bait. In a total of 48 soil samples, 41.7% were positive for the presence of entomopathogenic fungi. The isolates were belonging to the genera Beauveria, Metarhizium and Isaria, from order Hypocreales. It was found that the factors related to soil sampling location (region, period, and habitat) showed no significant difference in their variables for the presence of entomopathogenic fungi, however other soil factors (pH, amount of organic matter and argil) showed significance. The isolates were submitted to genetic variability analysis by RAPD markers, where 15 primers were selected, producing a total of 179 bands (Beauveria) and 131 bands (Metarhizium) and the similarity matrices were made using the Jaccard coefficient, which generated dendrogram by the UPGMA method, for each fungus. There was low genetic similarity among isolates of both genders. In this work, the entomopathogenic fungi isolated can be useful for biological control in agriculture once these isolates show certain persistence in adverse conditions of temperature, humidity and UV radiation.